Modelo de medición de un sistema de salud en una ciudad inteligente (2020)
A smart city is a dynamic system where its different dimensions constantly interact. A city is said to be smart when it solves its problems and manages to provide a better quality of life to its citizens (Khatoun & Zeadally, 2016) (Carvalho, n.d.) (Rjab & Mellouli, 2018) (United Nations, 2015). For this degree project, this definition is of great relevance since the proposal of a measurement system for a health system in a smart city and its associated maturity model will be based on it. Coming up with a proposal to measure the level of intelligence of a health system. Additionally, in this work it was defined that intelligence is associated with the generation of knowledge and the capacity of a city to solve its problems in an accelerated way. Regarding the quality of life, it can be improved in all the areas in which a citizen performs, however, the representatives of the member states of the united nations have defined a series of objectives that countries should achieve by 2030 on the global 2030 agenda. Among these goals, called the sustainable development goals or SDGs, is goal 3, "Health and well-being", which seeks to "Guarantee a healthy life and promote well-being for all at all ages" ( Organization of the united nations, 2017), which seeks to target the development of this undergraduate work, where a model will be provided that allows city leaders to know the degree to which they are achieving the sustainable development objective number 3 and other objectives that the city has in terms of health. In order to know to what extent the city is contributing to the fulfillment of the sustainable development objectives, it requires having a system of measures that allows it to know if it is managing to improve the quality of life with the actions it carries out. That is why in this work, a review will be made of the indicators currently used to measure the health systems in cities and then present a proposal that allows evaluating whether a city is achieving its objectives incrementally or intelligently. Additionally, a review of existing maturity models will be made so that a health system achieves intelligence, a proposed maturity model will be presented, and the city of Bogotá will be evaluated as a case study. At the end, a proposal for a measurement model of a health system in a smart city is found as a contribution to this project, where not only the state of a city is evaluated at a specific moment, but also how government actions have impacted the solution of your particular problems. Followed by this measurement model, a maturity model of a smart city is presented where the different steps that a city must take to reach intelligence can be observed, followed by a validation of the two models in the case of the Bogotá Study.